Rancang Bangun Prototipe Sistem Monitoring Suhu dan Kelembaban Gudang Berbasis Scada - Edhy Susanto; Tukadi Tukadi; Wahyu Setyo Pambudi (STMIK Budi Darma, 2021)
A warehouse to store goods requires parameters related to humidity and temperature. For rice to be durable in the warehouse, it is necessary to control and monitor these conditions to reduce the level of damage to rice. However, control and supervision must be carried out continuously, which results in a group of efficiency in terms of cost and time. The operator can do some control techniques by looking directly at and controlling by turning the heating or cooling machine on and off to condition the room with the settings. In this study, the implementation of SCADA was carried out by making a prototype of a temperature and humidity monitoring system in a warehouse using the AHT10 sensor. Temperature and humidity data can be stored in a computer used as a reference for controlling and analysing rice resistance in warehouses. As a reference, the stored rice is Bulog rice stored in a warehouse with temperature requirements not below 28 C and humidity not exceeding 55% based on references from previous studies. The system is equipped with fan PID control to lower the humidity and raise the temperature according to a set target. Using tuning with the Ziegler-Nichols method, the value of Kp 14.88 Ki 0.2976 Kd 186 is obtained at the temperature control, and the importance of Kp is 16.56 Ki 0.3312 Kd 207, and the error rate at temperature readings is 0.10096%, and humidity is 0.138%.